Approach to the poetic creation: Plato, Aristotle and Horace - Herrero de Miguel, Víctor (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Poetry has always aroused a feeling of fullness and mystery. Its ability to reach the exact center of things has been seen as proof of a mysterious origin. Where does this word that can lead us humans towards life’s greatest depths and heights come from? In the following pages, we’ll stop to examine the three authors who, in the Greco-Roman tradition, founded Western Poetics: Plato, Aristotle and Horace. To them we can trace the first critical effort to systematize the process of poetic creation. We’ve also learned from them that poetry is one of the most serious ways of inhabiting our world. By embracing their works, we discover the possibilities and the dangers that surround that long journeyed word of ours.
Keywords: Poetic word; divine source; human being; aesthetics; ethics.